Energy utilizability concept as a retrofitting solution selection criterion for buildings - Yang, Junjing; Chong, Adrian; Santamouris, Mat; Kolokotsa, Denia; Lee, Siew Eang; Tham, Kwok Wai; Sekhar, Chandra; Cheong, David Kok Wai (Journal of Civil Engineering and Management, 2017)
Retrofitting is widely explored as one of the energy conserving opportunities for existing buildings, in which both passive and active solutions are carefully evaluated. However, when different retrofitting solutions are combined and applied to a building, the total energy savings potential, which is less than the sum of the savings from applying the various individual retrofitting solutions, is considerably reduced and the synergies among the various technologies need to be understood and evaluated. In this study, the concept of utilizability is employed for the analysis of multiple energy retrofitting solutions in buildings and is defined as the ratio of energy savings derived from applying combined solutions to a building over the sum of individual energy savings from applying individual solutions. It is aimed at providing a better understanding of the combined retrofitting solutions. The sensitivity analysis on the utilizability value further provides a selection criterion for retrofitting solution selection.